DEVELOPMENT OF STRATEGIES FOR CANCER AWARENESS IMPROVEMENT IN THE COMMUNITY - Ahmad Saharrudin bin Mat Akir,; Engku Mardiah Engku Kamarudin,; Noor Syamilah Zakaria,; Siti Nordarma Ab. Rahman,; Mohd Imran Yusoff, (Journal of Contemporary Social Science and Education Studies (JOCSSES) E-ISSN- 2785-8774, 2024)
This study aims to identify and analyze the main factors that influence cancer awareness at the community level. Using a multidimensional approach, this study assessed the personal, behavioral, and environmental elements associated with cancer awareness. Data were collected through expert consensus assessment, with results presented in three tables that include personal, behavioral, and environmental aspects. The results of the study show that "Outcome Expectations" are the most important personal factors, while "Health Management Behaviors" and "Supportive Behaviors" appear as critical behavioral elements. In terms of environment, "Social Environment" was identified as the most influential factor. All these factors reached 100% consensus among the experts involved. These findings highlight the importance of a holistic approach to raising cancer awareness, which combines strategies that target personal, behavioral, and environmental aspects. This study suggests that effective cancer awareness programs should focus on the development of positive outcome expectancies, increasing self-efficacy, encouraging proactive health behaviors, and strengthening a supportive social environment. The implications of this study include the development of cancer awareness interventions that are more comprehensive and tailored to the needs of the community. Further research is suggested to explore the interaction between these factors and examine the long-term effectiveness of programs that address multiple dimensions of cancer awareness simultaneously.